Craniofacial Reconstruction of a 4000-year-old Human Skull - Lyu Tu; Li Shiwei; Li Caixia; Wei Xingtao; Zhang Jiaxin; Xu Ran; Bai Zhixin; Ji Yuan; Zhao Dong (Journal of Forensic Science and Medicine)
Craniofacial reconstruction (CFR) is a traditional technology used in forensic science and archaeology. CFR recovers the craniofacial appearance to approximate the appearance of missing persons or ancient humans. To reconstruct the craniofacial appearance of a 4000-year-old skull of a person who lived during the Longshan period of Chinese history, we performed CFR using a protective method. The skull was scanned and three dimensionally printed. Subsequently, morphological measurements were carried out. Traditional steps, such as sculpturing of the facial soft tissues, and facial features, and the creation of a cast skull model, were still essential for the complete outcome. Three-dimensional scanning and printing progressed the CFR to the digital stage, which avoided probable breaks during the traditional procedures and improved precision and efficacy. Although CFR is a scientific method with anatomical and anthropometry bases, it still requires expert experience in sculpture, history, and photography.